Effect of Spirulina platensis on Lipid Profile of Long Evans Rats - Mridha, M Omar Faruq; Noor, Parvin; Khaton, Rahima; Islam, Dipa; Hossain, Motaher (Bangladesh Journal of Scientific and Industrial Research, 2010)
To study the Effect of Spirulina platensis on lipid profile of Long Evan rats, an experiment was conducted by feeding the rats with diets supplemented with Spirulina platensis dry powder. Five different types of diets were included in the feeding. Group A containing high fat and high sugar considered as control-01. Group B with high fat, high sugar and 0.5% Spirulina. Group C with high fat, high sugar and 2.5% Spirulina. These three groups were included in Diet-1. Group D with laboratory diets considered as control-02 and Group E i.e., laboratory diet with Spirulina 150mg/kg/body weight. These two groups were included in Diet-2. This study describes the useful effect of Spirulina powder after administration in high fat and high sugar diet and in normal laboratory diet. Spirulina platensis powder showed an effective result in the lipid profile of Long Evan rats. Total cholesterol (TC) serum lipid significantly reduced in Group B than that of 2.5% of Spirulina powder in Group C rats. 0.5% and 2.5% Spirulina powder had the same effect in dropping low density lipoprotein (LDL) in both B and C Groups of rats. Conversely 2.5% Spirulina powder was found more effective in increasing high density lipoprotein (HDL) in Group C (50.54%) rats than the group B (24.18%) rats. On the other hand, the dose 150mg/kg b.w Spirulina powder mixed in laboratory diet showed an effective result in decreasing total cholesterol (TC) and low density lipoprotein (LDL) 19.21% and 46.06%, respectively. The findings clearly indicated that 150mg/kg b.w Spirulina powder had positive effect to increase the value of high density lipoprotein (HDL) in Group E (24.98%) rats compare to control group D rats. There were no significant differences in diet-1 groups' TC, TG and LDL-C of the groups of A (control- 01), B and C (p<0.05), although they varies statistically for HDL among these groups (p>0.05). On the other hand in diet-2 groups' TG, LDL and HDL of E groups of rats were significantly varies than control-2 groups of rats D ( p>0.05), although TC was not significant statistically (p<0.05). Keywords: High fat diet; Body weight (b.w); Hypercholesterolemia; Hypolipidaemic; Spirulina platensis. DOI: 10.3329/bjsir.v45i3.6533 Bangladesh J. Sci. Ind. Res. 45(3), 249-254, 2010